Analysis of Structures and Epitopes of Surface Antigen Glycoproteins Expressed in Bradyzoites of Toxoplasma gondii. (21st March 2013) - Cong, Hua; Zhang, Min; Zhang, Qingli; Gong, Jing; Cong, Haizi; Xin, Qing; He, Shenyi
Abstract : Toxoplasma gondii is a protozoan parasite capable of infecting humans and animals. Surface antigen glycoproteins, SAG2C, -2D, -2X, and -2Y, are expressed on the surface of bradyzoites. These antigens have been shown to protect bradyzoites against immune responses during chronic infections. We studied structures of SAG2C, -2D, -2X, and -2Y proteins using bioinformatics methods. The protein sequence alignment was performed by T-Coffee method. Secondary structural and functional domains were predicted using software PSIPRED v3.0 and SMART software, and 3D models of proteins were constructed and compared using the I-TASSER server, VMD, and SWISS-spdbv. Our results showed that SAG2C, -2D, -2X, and -2Y are highly homologous proteins. They share the same conserved peptides and HLA-I restricted epitopes. The similarity in structure and domains indicated putative common functions that might stimulate similar immune response in hosts. The conserved peptides and HLA-restricted epitopes could provide important insights on vaccine study and the diagnosis of this disease.